1999
DOI: 10.1143/jjap.38.6272
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Magnetoresistance of Granular Evaporated Fe/Si Films

Abstract: The independent-atom model (IAM) together with partial waves has been used to study the eKect of the absorption potential on the elastic scattering of electrons bythe carbon tetrafluoride molecule in the incident energy range 100-700eV. The atom is represented by an optical potential which is complex, spherically symmetric and energy dependent. The differential, integral elastic and momentum transfer cross sections have been obtained. The present results are in good agreement with the available experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…After 24 ML the MR still decreases with growing number of Si layers. It is obvious, however, that a reasonably large MR remains even for thick spacers, which is in disagreement with the known experimental …ndings [Tong et al (1999); Ihara et al (1999);Inomata et al (1995)]. It is suggested that the origin of this discrepancy is similar to what has been discussed in the case of the IEC.…”
Section: Perpendicular Electric Transportmentioning
confidence: 69%
See 3 more Smart Citations
“…After 24 ML the MR still decreases with growing number of Si layers. It is obvious, however, that a reasonably large MR remains even for thick spacers, which is in disagreement with the known experimental …ndings [Tong et al (1999); Ihara et al (1999);Inomata et al (1995)]. It is suggested that the origin of this discrepancy is similar to what has been discussed in the case of the IEC.…”
Section: Perpendicular Electric Transportmentioning
confidence: 69%
“…In most systems these interdi¤usion e¤ects at the interfaces are important for the IEC and as well as for the transport properties [Gareev et al (2001); Ihara et al (1999)]. In order to study the in ‡uence of interdi¤usion additional investigations have been carried out for systems of the type where s is the total number of Si layers.…”
Section: Computational Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, metal-semiconductor hybrid systems such as Fe/Si and GaAs/Co have been extensively studied because of their potential application in electronics [2][3][4][5]. Recently, Dinia et al [6] and Ihara et al [7] reported very small inverse magnetoresistance, where the resistance is smaller at zero field than the saturation field, in Fe/Si films.…”
mentioning
confidence: 99%